2009
DOI: 10.4103/0255-0857.55449
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Microbial Resistance Stratified by Risk Factor Among Escherichia Coli Strains Isolated From the Urinary Tract at a Rural Clinic in Central India

Abstract: under intense selection pressure in the hospital environment.In the course of our work in central India, with a predominantly rural population that has poor access to healthcare, we have seen failure of empirical treatment of community-acquired UTIs with commonly-used, orallyadministered drugs in more than a third of cases. This happens regardless of the presence of complicating factors. Failure of empirical treatment of nosocomial UTI occurs even more frequently.The aim of the present study was to document re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
1
8
0
2
Order By: Relevance
“…[41517] Similarly, all uropathogens in the present study showed a high resistance to 1 st , 2 nd and 3 rd generation cephalosporins (44-100%), while other studies have reported a comparatively lower resistance. [11524] The high resistance to fluroquinolones and cephalosporins in the present study can be attributed to the easy access and indiscriminate use of these drugs for all types of infections, and emphasizes the role of selective drug pressure in emergence of drug-resistant mutants. It is recommended that these drugs should not be considered as first-line therapy for the empiric treatment of UTIs in this part of the country, as opposed to that recommended by other studies both from India and from abroad.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…[41517] Similarly, all uropathogens in the present study showed a high resistance to 1 st , 2 nd and 3 rd generation cephalosporins (44-100%), while other studies have reported a comparatively lower resistance. [11524] The high resistance to fluroquinolones and cephalosporins in the present study can be attributed to the easy access and indiscriminate use of these drugs for all types of infections, and emphasizes the role of selective drug pressure in emergence of drug-resistant mutants. It is recommended that these drugs should not be considered as first-line therapy for the empiric treatment of UTIs in this part of the country, as opposed to that recommended by other studies both from India and from abroad.…”
Section: Discussionsupporting
confidence: 63%
“…[91013] However, studies from some other parts of the country have shown higher isolation rates (65% to more than 90%). [151617] This difference probably occurred because ours is a tertiary care center as compared with the primary and secondary care levels of these centers.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to the studies conducted by other researchers 16,21,22 . However, studies from some other parts of the country had shown higher frequency rates (65-90%) [23][24][25] . This variation might be due to the different environmental conditions in different areas.…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms were initially identified using the colony characters on the above medias and Gram staining, Stock cultures were maintained at 4 o C on nutrient agar. The bacterial strains were identified by performing IMViC tests 8 , and extended biochemical reactions like catalase, oxidase, H 2 S production, urease test 9 .…”
Section: Isolation and Identification Of Uropathogensmentioning
confidence: 99%
“…Gelatinase production was tested using gelatin agar 9 . Production of beta lactamases was determined by iodometric method by Sng et al, 1980 13 .…”
Section: Evaluation Of Virulence Phenotypesmentioning
confidence: 99%